QUALITY ATTRIBUTES IN COST MANAGEMENT AND ACCOUNTING SUBJECTS: THE STUDENTS’ VIEWPOINT - Tibola, Jucelia Appio (Conselho Federal de Contabilidade (CFC), 2018)
The aim in this research is to identify the quality attributes students perceive in cost management and accounting subjects. The subjects were 126 students who took the subjects Cost Applied to Administration, Cost Accounting and Cost Analysis, corresponding to all students in the semester during which the research was undertaken. Thus, a census study was adopted. The research institution is a public university that offers graduate (M.Sc. and Ph.D.) programs in Accountancy and Business Administration, particularly in the South of Brazil. An exploratory and qualitative research design was used in the first part and a descriptive and quantitative design in the second. Data were collected with the help of a structured questionnaire with open questions, applying the Critical Incident Technique. Content Analysis was used to classify and categorize the respondents’ answers into units of meaning. In the second phase, these categories were transformed into categorical variables and analyzed through statistical procedures. The results evidenced that the quality attributes constituted an Axis. In the Cost Analysis subjects, they privileged the lecturer’s quality. In Cost Accounting, the students evidenced the teacher’s commitment and the application of practical examples as a relevant attribute. In Cost Applied to Administration, the results indicated that understanding about the subject, clarification of doubts and the lecturer’s didactics served as quality attributes..